Construction heuristics for the single row layout problem with machine-spanning clearances. Issue 1 (2nd January 2019) - Keller, B.
ABSTRACT: The single row layout problem (SRLP) consists of finding an efficient arrangement of n machines arranged along one side of the material transportation path including clearances between machines. Undesired interactions between machines necessitate large clearances not only considered between adjacent machines, but also between machines arranged further away from each other. This new type of clearances, termed machine-spanning clearances, is considered in this paper. Based on previous works for the SRLP, a modified mathematical model of this problem is established in order to minimize the weighted sum of distances. To generate an initial solution, three construction heuristics are proposed and their performance is tested on several instances newly generated or taken from literature. Their results show that all of them perform well regarding the solution quality as well as the computational efficiency.